2022
DOI: 10.3389/fcvm.2022.853427
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Short-Term Autonomic and Hemodynamic Responses to Transcranial Direct Current Stimulation in Patients With Resistant Hypertension

Abstract: Previously, we demonstrated that acute transcranial direct current stimulation (tDCS) reduced blood pressure (BP) and improved autonomic modulation in hypertensives. We hypothesized that acute and short-term tDCS intervention can promote similar benefits in resistant hypertensive patients (RHT). We assessed the impact of one (acute intervention) and ten (short-term intervention) tDCS or SHAM (20 min, each) sessions on BP, pulse interval (PI) and systolic blood pressure variabilities, humoral mechanisms associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“… 10 Recently, a Brazilian group demonstrated that the acute transcranial direct current stimulation (tDCS), a noninvasive procedure, decreased central and peripheral hemodynamic parameters and improved autonomic modulation in individuals with RH. 30 Apparently, both methods (TENS and tDCS) present the same pathophysiological basis for reducing the central and peripheral BP, possibly mediated by autonomic modulation.…”
Section: Discussionmentioning
confidence: 98%
“… 10 Recently, a Brazilian group demonstrated that the acute transcranial direct current stimulation (tDCS), a noninvasive procedure, decreased central and peripheral hemodynamic parameters and improved autonomic modulation in individuals with RH. 30 Apparently, both methods (TENS and tDCS) present the same pathophysiological basis for reducing the central and peripheral BP, possibly mediated by autonomic modulation.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, there may be broader benefits associated with using tCDS extending to treating refractory hypertension. The initial investigation on the effects of tDCS on systemic blood pressure revealed a significant reduction as measured by 24 h ABPM, potentially mediated by cardiovascular autonomic balance ( 171 ). While it has shown promise in treating various neurological conditions like depression and chronic pain, its efficacy in addressing hypertension requires further study.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…No entanto, nada sugeriu mudanças significativas nos valores de variabilidade. Um terceiro estudo de Rodrigues et al 15 envolveu 13 participantes com HAS resistente. Com um intervalo de pouco menos de 1 mês, avaliou uma intervenção aguda e uma intervenção de curto prazo.…”
Section: Arêas Et Al Neuromodulação No Tratamento Da Hipertensãounclassified
“…A third study by Rodrigues et al 15 involved 13 participants with resistant arterial HTN. At an interval of just under 1 month, it evaluated an acute intervention and a short-term intervention.…”
mentioning
confidence: 99%